2021
DOI: 10.3389/fonc.2021.740796
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib: A Promising Proteasome Inhibitor for the Treatment of Relapsed and Refractory Multiple Myeloma

Abstract: The proteasome is crucial for the degradation of intracellular proteins and plays an important role in mediating a number of cell survival and progression events by controlling the levels of key regulatory proteins such as cyclins and caspases in both normal and tumor cells. However, compared to normal cells, cancer cells are more dependent on the ubiquitin proteasome pathway (UPP) due to the accumulation of proteins in response to uncontrolled gene transcription, allowing proteasome to become a potent therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 127 publications
(240 reference statements)
0
32
0
Order By: Relevance
“…The proteasome system is the main protein disposal system in cells for the degradation of denatured proteins, and the proteasome-mediated hydrolysis of more than 80% of all cellular proteins determines their cell survival [ 3 ]. Proteasome inhibitors, such as carfilzomib, are utilized to treat multiple myeloma and effectively induce cell death in cancer cells [ 3 , 4 ]; therefore, proteasomes are a promising target in the establishment of effective cancer treatment strategies. Moreover, a recent study revealed the overexpression of proteasomal subunits in MM tissues [ 5 ], indicating the potential of proteasomes as a target in the treatment of MM.…”
Section: Introductionmentioning
confidence: 99%
“…The proteasome system is the main protein disposal system in cells for the degradation of denatured proteins, and the proteasome-mediated hydrolysis of more than 80% of all cellular proteins determines their cell survival [ 3 ]. Proteasome inhibitors, such as carfilzomib, are utilized to treat multiple myeloma and effectively induce cell death in cancer cells [ 3 , 4 ]; therefore, proteasomes are a promising target in the establishment of effective cancer treatment strategies. Moreover, a recent study revealed the overexpression of proteasomal subunits in MM tissues [ 5 ], indicating the potential of proteasomes as a target in the treatment of MM.…”
Section: Introductionmentioning
confidence: 99%
“…The drug carfilzomib is known to treat small lung cancer. Interestingly, it is reported that carfilzomib is a promising proteasome inhibitor for the treatment of relapsed and refractory multiple myeloma [ 67 ]. The three-dimensional representation of the ligand binding to the pocket of TMPRSS2 is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Second-generation proteasome inhibitors (PIs) were developed to overcome bortezomib resistance as well as improved efficacy and safety and convenient methods of administration ( Kisselev et al., 2012 ; Fricker, 2020 ). Carfilzomib (Onyx/Amgen) is derived from epoxomicin, – a tetrapeptide epoxyketone natural product isolated from Actinomyces ( Kuhn et al., 2007 ; Huber and Groll, 2012 ; Kisselev et al., 2012 ; Herndon et al., 2013 ; Park et al., 2018 ; Fricker, 2020 ; Jayaweera et al., 2021 ). Carfilzomib is FDA-approved as a single agent for treatment of refractory MM, specifically those who had received >2 prior lines of therapy and have progressed on or within 60 days of completion of their last therapy ( Kuhn et al., 2007 ; Herndon et al., 2013 ; Park et al., 2018 ).…”
Section: Targeting the Proteasome In Cancer Treatmentmentioning
confidence: 99%
“…Importantly, proteasome inhibition drives formation of intracellular inclusions known as the aggresome, protein aggregates that tend to be refractory to proteolysis and to accumulate in inclusion bodies (Kawaguchi et al, 2003). Aggresome (Kuhn et al, 2007;Huber and Groll, 2012;Herndon et al, 2013;Park et al, 2018;Jayaweera et al, 2021) Tetrapeptide epoxyketone…”
Section: Proteasomes In Autoinflammatory Syndromes and Neurodevelopme...mentioning
confidence: 99%